Established Pseudomonas syringae pv. tomato infection disrupts immigration of leaf surface bacteria to the apoplast - Cowles, Kimberly N.; Iyer, Arjun S.; McConnell, Iain; Guillemette, Ellie G.; Nellore, Dharshita; Zaacks, Sonia C.; Barak, Jeri D. (Frontiers in Microbiology, 2025)
Bacterial disease alters the infection court creating new niches. The apoplast is an oasis from the hardships of the leaf surface and is generally inaccessible to nonpathogenic members of the phyllosphere bacterial community. Previously, we demonstrated that Salmonella enterica serovar Typhimurium (S. Typhimurium) immigrants to the leaf surface can both enter the apoplast and replicate due to conditions created by an established Xanthomonas hortorum pv. gardneri (Xhg) infection in tomato. Here, we have expanded our investigation of how infection changes the host by examining the effects of another water-soaking pathogen, Pseudomonas syringae pv. tomato (Pst), on immigrating bacteria. We discovered that, despite causing macroscopically similar symptoms as Xhg, Pst infection disrupts S. Typhimurium colonization of the apoplast. To determine if these effects were broadly applicable to phyllosphere bacteria, we examined the fates of immigrant Xhg and Pst arriving on an infected leaf. We found that this effect is not specific to S. Typhimurium, but that immigrating Xhg or Pst also struggled to fully join the infecting Pst population established in the apoplast. To identify the mechanisms underlying these results, we quantified macroscopic infection symptoms, examined stomata as a pinch point of bacterial entry, and characterized aspects of interbacterial competition. While it may be considered common knowledge that hosts are fundamentally altered following infection, the mechanisms that drive these changes remain poorly understood. Here, we investigated these pathogens to reach a deeper understanding of how infection alters a host from a rarely accessible, inhabitable environment to an obtainable, habitable niche.